2011
DOI: 10.4304/tpls.1.7.778-784
|View full text |Cite
|
Sign up to set email alerts
|

The Reading Strategies Awareness among English as a Second Language (ESL) Learners in Malaysia’s University

Abstract: Abstract-This research paper aims to measure the awareness level of reading strategies of the English as Second Language (ESL) Learners in Universiti Teknologi MARA, Penang. This study has included the measurement of their perceived use of reading strategies while reading academic materials since reading of specialized academic material in the second language is beginning to receive attention. This type of academic reading is also important to test the learners' reading comprehension skills and their knowledge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 3 publications
3
4
0
Order By: Relevance
“…In addition, the sequence pattern of reading strategies subscales by the students fell into Problem Solving Strategies followed by Global Reading Strategies, and Support Reading Strategies which were similar to previous studies (Poole, 2005;Li, 2010;Aziz, et al, 2011;Riazi & Alhaqbani, 2012;Magogwe, 2013;Ahmad, 2015;and Alami, 2016) which employed SORS questionnaire to investigate the use of reading strategies in different contexts. However, there was no clear explanation of why the similarities of preference occurred among EFL and EFL students.…”
Section: Discussionsupporting
confidence: 80%
“…In addition, the sequence pattern of reading strategies subscales by the students fell into Problem Solving Strategies followed by Global Reading Strategies, and Support Reading Strategies which were similar to previous studies (Poole, 2005;Li, 2010;Aziz, et al, 2011;Riazi & Alhaqbani, 2012;Magogwe, 2013;Ahmad, 2015;and Alami, 2016) which employed SORS questionnaire to investigate the use of reading strategies in different contexts. However, there was no clear explanation of why the similarities of preference occurred among EFL and EFL students.…”
Section: Discussionsupporting
confidence: 80%
“…This finding concerning moderate overall use of reading strategies is compatible with the findings of Sheorey and Mokhtari (2001), who administered the SORS to a group of ESL learners coming from different L1 backgrounds along with a group of native speakers of English, and Aziz et al (2011), in which sixty Malay learners of English responded the same survey. On the other hand, the present study slightly differs from Chumworatayee (2012), who used SORS to measure the students' metacognitive awareness of reading strategies while reading academic materials, in the sense that there is a minor difference between the overall score average of the reading strategies in the present study (M=3.40, Moderate overall use of reading strategies) and the Chumworatayee's (2012) study (M=3.54, High overall use of reading strategies).…”
Section: Discussionsupporting
confidence: 78%
“…This finding is in line with Aziz et al (2011) andChumworatayee (2012), who also reported that Malay EFL learners and Thai EFL learners respectively used problem-solving strategies more often than global reading strategies and than supplementary reading strategies. However, the present study differs from Sheorey and Mokhtari (2001) and Tercanlıoğlu (2004), who stated that EFL/ESL learners employ global reading strategies more often than problem-solving strategies.…”
Section: Discussionsupporting
confidence: 78%
“…They will be more proficient readers, as these strategies aid them to read accurately and follow the text more closely. Aziz et al (2011) also added that these strategies give students an idea of the content and message in the text. All these clearly indicate that without ESL reading strategies, students will face challenges in comprehending the reading comprehension texts.…”
Section: Esl Reading Strategiesmentioning
confidence: 99%